Estudo comparativo dos portadores de cardiopatia chagásica crônica versus cardiopatia não-isquêmica com desfibrilador cardíaco implantável - Gondim, Francisca Tatiana Pereira (2024)
Chagas disease is a serious public health problem. Sudden cardiac death (SCD) due to malignant ventricular arrhythmia is responsible for 50% of deaths in chronic Chagas heart disease (CCD). The implantable cardioverter defibrillator (ICD) has become the main therapeutic strategy for preventing sudden cardiac death (SCD). However, the efficacy and safety of treating chagasic patients with ICDs has been evaluated in few observational studies. The objective of the present work was to comparatively analyze patterns of morbidity, mortality and survival in cases with CDI in cohorts with CCC and non-ischemic heart disease (NIC) treated at a single reference university hospital in the state of Ceará. Design, population and methods: this is a cohort historical. The population consisted of patients with CCC and ICD for primary or secondary prophylaxis of death. The outcomes analyzed were appropriate activation of the ICD (shocks, electrical storms, antitachycardia-ATP therapies and appropriate therapies), mortality and its predictive factors. For comparative analysis, patients with NIC and CDI for primary or secondary prophylaxis of sudden death were included. Results: 207 patients were included, 117 with CCC and 90 with NIC. The median follow-up time (months) was similar in both groups, 62(25-121) in CCC and 56.5(23-119) in NIC. Males predominated in CCC compared to CNI (p=0.028). The groups did not differ statically in median age at the time of ICD implantation. The level of education was lower in patients with CCC (p<0.001) as was the monthly family income (p<0.001). Secondary prevention was the most prevalent condition 61.8% that determined the implantation of ICD devices. Normal left ventricular ejection fraction (p=0.01) was more prevalent in CCC. Functional class III/IV (p<0.001) were more prevalent in NIC than in CCC. The incidence of appropriate shock (p<0.001), appropriate shock associated with ATP (p=0.022), ATP (p=0.006), electrical storm (p=0.005) and inappropriate shock (p=0.045) were higher in patients with CCC .Secondary prevention was a predictor of ICD activation in both CCC and CNI. Having CCC increased the risk of having appropriate shock by 2.4 times (95% CI: 1.4-4.2; p=0.002), 2.6 times of having ATP (95% CI: 1.3-5.3; p=0.008) and 2.5 times of having an appropriate shock associated with ATP (95% CI: CI 1.1- 5.8; p=0.032) when compared to those with NIC. During follow-up, 39.3% (46 patients) died at CCC and 5.6% (05 patients) in the NIC. The total annual mortality rate was 6.2% (95% CI: 0.046-0.083) in CCC and 0.8% (95% CI: 0.003-0.021) in NIC. Having CCC increased the risk of death by 6.9 times when compared to NIC (95% CI: 2.8 - 17.5; p<0.001). During follow-up we had only two sudden deaths, these in CCC. Left ventricular ejection fraction less than 30%, functional class IV and age over 75 years were predictors of mortality in CCC. Conclusion: CCC is a complex disease, which affects people with greater social vulnerability, has an incidence discharge from appropriate ICD therapies and death in relation to NIC. This demonstrates a high and peculiar arrhythmogenic potential in patients with CCC. Our study also suggests that the ICD is safe and effective in patients with CCC as we had a low rate of SCD despite a high number of ICD therapies